Exploring the in vitro antimicrobial, antioxidant, and anticancer potentials of Spinifex littoreus Burm f. Merr. against human cervical cancer - Vedhamani, J; Ajithkumar , I Paul; Jemima, E Angel (Plant Science Today, 2024)
Spinifex littoreus Burm f. Merr. is considered as a pharmaceutically important coastal weed whereas, therapeutical applications of this plant are least studied. The current study aimed to identify the antibacterial, antioxidant, and anticancer properties in the chloroform extract of Spinifex littoreus. Six bacterial and 4 fungal human infections were tested for antibacterial activity in the chloroform extract of S. littoreus (SL-CH). The antioxidant ability of SL-CH was screened using the DPPH, ABTS, and H2O2 assays. MTT assay was used to investigate the anticancer activity of SL-CH and ROS, Annexin V, PI, and cell cycle analysis were used to determine its efficacy. The bacterial strain Propionibacterium acnes and the fungal strain Sporothrix schenckii were found to have the largest zones of clearance when the SL-CH extract was used at a concentration of 500 µg/ml. The antioxidant potentials of SL-CH extract showed the maximum radical scavenging activity against ABTS (83.98%), H2O2 (63.73%), and DPPH (52.02%) and their IC50 value was 31.74 ?g/ml, 53.93 ?g/ml, and 139.6 ?g/ml respectively. The IC50 concentration for the chloroform extract of Spinifex littoreus was determined to be 117.5 µg/ml and it showed concentration-dependent anticancer activity against HeLa cells. The ROS fluorescence staining result of SL-CH demonstrated the production of reactive oxygen species, which caused HeLa cells to undergo apoptosis. It was demonstrated by annexin V staining, PI staining technique, and cell cycle analysis that SL-CH extracts caused apoptosis in HeLa cells, preventing their growth. Taken together, these results showed that Spinifex littoreus chloroform extract is rich in antimicrobial, antioxidant, and anticancer potentials. Therefore, Spinifex littoreus extract can treat and prevent various ailments.